Evaluation of spatial PD1 and PD-L1 expression in inflammatory bowel disease samples – a pilot study - Szczepaniak, Kinga; Paskal, Wiktor; Kuśmierczyk, Zofia; Wejman, Jarosław; Ostrowska, Joanna; Tarnowski, Wiesław; Włodarski, Paweł (Polish Journal of Pathology, 2022)
Alterations of PD1/PD-L1 pathway may be associated with an excessive inflammatory response in the intestinal wall in inflammatory bowel diseases (IBD). To evaluate the expression of PD-1 and PD-L1 in 4 compartments of intestinal wall (mucosa, submucosa, muscularis propria and lymphatic follicles), high-resolution immunohistochemically stained slides were obtained from formalin-fixed paraffin-embedded samples of 10 Crohn’s disease (CD), 9 ulcerative colitis (UC) and 10 unaffected individuals cases. The levels of expression were quantified using the QuPath software. PD-1 was detected in lymphatic follicles in affected and unaffected tissue samples and in inflammatory infiltration in IBD. There was no difference between groups neither in PD-1 overall expression nor in individual compartments, with the exception of the mucosal expression. It was higher in the mucosa of CD patients comparing to controls, however this difference was marginal (p = 0.0461). PD-L1 was expressed in endothelium and mesenteric nervous plexi, consistently in each group. There were no significant differences in PD-L1 immunoreactivity in context of histologic compartment nor clinical diagnosis. The results suggest that PD-1 and PD-L1 expression in intestinal tissue is heterogeneous in the analysed groups, thus it may be dependent on individual characteristics.